Future possibilities of Irish agriculture - Kennedy, Henry (Statistical and Social Inquiry Society of Ireland, 1938)
In a country lacking any considerable resources of raw material, with but a limited export trade in industrial products, but having a fertile soil and favourable climate, it is to increased production on the land that one must look for the resources to provide more wealth and a higher standard of living for the entire population. It is extremely doubtful if the volume of production has increased appreciably in the last quarter of a century. There is a real danger that production may diminish as a result of the disparity of price against cost of production, and as a result of the want of balance between economic conditions on the land and in urban or industrial employment in this country and in Great Britain. It is essential to counteract this tendency in time, and the need is so real as to justify exceptional measures of relief. The necessity of relief measures makes it all the more urgent to examine whether it is possible to enable farmers to reduce costs of production, so as to restore the balance between costs and receipts, and thereby restore the balance of opportunity as between rural and urban employment. In my view, much of this object can be achieved by a new technique of production, and at the same time a very desirable increase in production can be effected.
Read on Thursday, 11th February, 1938
Keywords: Agricultural productivity; Irish agriculture; 314.15